Tafsir Politik: Studi terhadap Pemikiran Politik Hamka dan Pengaruhnya dalam Tafsir Al-Azhar - Halimatussa'diyah Halimatussa'diyah; Abdul Kher; Rahmat Hidayat; Sulaiman Mohammad Nur (Jurnal Semiotika Quran, 2024)
This article aims to reveal Hamka's political thoughts and their influence on interpretation. Many  predictions  can  be made to the figure of Hamka. Hamka is not only known as a writer, columnist, but Hamka is also popular as a scholar, mufassir and politician. Hamka in conveying his ideas, not only verbally but also in writing. This is  evident  in  the  large  number  of Hamka's  works  from various scholars. Hamka's popular and phenomenal work is Tafsir al-Azhar. As someone involved in practical politics, gave Hamka an influence in interpreting the Koran. Among Hamka's ideas in Tafsir al-Azhar are related to politics. The findings of this study are that according to Hamka, the order for deliberation is contained in the al-Qur'an, however al-Qu'an does not explain in detail the implementation of the deliberation. The implementation of deliberations depends on the situation and condition of the community. In the election of the head of state, Hamka argued that the requirements for the head of state were people of faith. The reason Hamka is the head of state chosen by a believer is because the head of state is not a believer (non-Muslim) can invite him to taghout. There is no separation between state and religion in the relationship between state and religion. Islam requires a harmonious relationship between religion and state.